Tissue Damage Caused by Myeloablative, but Not Non-Myeloablative, Conditioning before Allogeneic Stem Cell Transplantation Results in Dermal Macrophage Recruitment without Active T-Cell Interaction - van Balen, Peter; van der Zouwen, Boris; Kruisselbrink, Alwine B.; Eefting, Matthijs; Szuhai, Karoly; Jordanova, Ekaterina S.; Falkenburg, J. H. F.; Jedema, Inge (Frontiers in Immunology, 2018)
Introduction Conditioning regimens preceding allogeneic stem cell transplantation (alloSCT) can cause tissue damage and acceleration of the development of graft-versus-host disease (GVHD). T-cell depleted alloSCT with postponed donor lymphocyte infusion (DLI) may reduce GVHD because tissue injury can be restored at the time of DLI. In this study, we investigated the presence of tissue injury and inflammation in skin during the period of hematologic recovery and immune reconstitution after alloSCT. Methods Skin biopsies were immunohistochemically stained for HLA class II, CD1a, CD11c, CD40, CD54, CD68, CD86, CD206, CD3 and CD8. HLA class II expressing cells were characterized as activated T-cells, antigen presenting cells (APC) or tissue repairing macrophages. In sex mismatched patient and donor couples, origin of cells was determined by multiplex analysis combining XY-FISH and fluorescent immunohistochemistry. Results No inflammatory environment due to pretransplant conditioning was detected at the time of alloSCT, irrespective of the conditioning regimen. An increase in HLA class II positive macrophages and CD3 T-cells was observed 12-24 weeks after myeloablative alloSCT, but these macrophages did not show signs of interaction with the co-localized T-cells. In contrast, during GVHD, an increase in HLA class II expressing cells coinciding with T-cell interaction was observed, resulting in an overt inflammatory reaction with presence of activated APC, activated donor T-cells and localized upregulation of HLA class II expression on epidermal cells. In the absence of GVHD, patient derived macrophages were gradually replaced by donor derived macrophages, although patient derived macrophages were detectable even 24 weeks after alloSCT. Conclusion Conditioning regimens cause tissue damage in the skin, but this does not result in a local increase of activated APC. In contrast to the inflamed situation in GVHD, when interaction takes place between activated APC and donor T-cells, the tissue damage caused by myeloablative alloSCT results in dermal recruitment of HLA class II positive tissue repairing macrophages co-existing with increased numbers of patient and donor derived T-cells, but without signs of specific interaction and initiation of an immune response. Thus, the local skin damage caused by the conditioning regimen appears to be insufficient as single factor to provoke GVHD induction.